Analisis Konsentrasi Spasial Kemiskinan Di Jawa = Spatial Concentration Analysis of Poverty in Java - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The goal of this research is to show a descriptive pattern of spatial concentration of poverty in Java, measuring inequalities in the Java regions before and after the economic crisis, comparing inequalities in poverty rate between that which happens in the Island of Java and that outside of Java, within Indonesia, and to examine the extent of spatial concentration of poverty explained by economic, education, health, and demographic dimensions. Poverty rate was divided into three categories. The three categories are regions with high poverty rate (more than 40 percent), moderate (20-40 percent), and low poverty rate (less than 20 percent). These three categories are then analyzed by Multiple Discriminant Analysis to find the variables that will differentiate between three categories. Inequalities between regions measured using The entropy index of inequality. The results of this research show that almost every regency and municipality in Java experienced a higher poverty rate in 1999 than in 1996, and have a geographically disparate poverty distribution pattern because of the wide range of poverty variation in Java during the time of crisis. Both in 1999 and 1996, the disparity index values within region (province) were calculated to be larger than disparity index value between regions (province). This shows that the spatial concentration of poverty between regency and municipality in Java within one province is higher compared to the spatial concentration between provinces. In other words, the spatial concentration of poverty in Java generally congregates in municipalities or regencies. From the results of the discriminant analysis it is concluded that the poverty rate category in Java can be differentiated significantly by the per capita income, wage rate, average education level, population density, and unemployment rate.